1981
DOI: 10.1530/acta.0.0970157
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the biological and immunological properties of human follitropin: profiles of two international reference preparations and of an aqueous extract of pituitary glands after electrofocusing

Abstract: Abstract. Two international reference preparations, the First International Reference Preparation of Human Pituitary Gonadotrophins (FSH and LH/ICSH) for Bioassay (identified hereafter by its code no.: 69/104) and the First International Standard of Urinary FSH and LH (ICSH) for Bioassay (hereafter: hMG 1st IS) and an aqueous extract of human pituitary glands (hPE) were fractionated in triplicate by isoelectric focusing on sucrose density gradient (Ampholine, pH range 2.5–10.0). The FSH activity was monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Studies performed on hFSH extracted from AP glands or urine have revealed the presence of several FSH species as disclosed by isoelectric focusing (253,258,262,270). Since the majority of these studies have been performed on pituitary hFSH preparations that have been exposed to chemical manipulation during their partial or total purification, comparisons with studies in other species that utilize crude pituitary extracts are questionable.…”
Section: Separation Of Fsh Forms and Determination Of Physiological Smentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed on hFSH extracted from AP glands or urine have revealed the presence of several FSH species as disclosed by isoelectric focusing (253,258,262,270). Since the majority of these studies have been performed on pituitary hFSH preparations that have been exposed to chemical manipulation during their partial or total purification, comparisons with studies in other species that utilize crude pituitary extracts are questionable.…”
Section: Separation Of Fsh Forms and Determination Of Physiological Smentioning
confidence: 99%
“…It has recently been demonstrated that gonadotropins exist in multiple forms which exhibit differences in biological, receptor binding and immunological activities (240,242,251,252). Multiple species of gonadotropins have been isolated and characterized from AP glands (72, 86, 238, 252), urine (242,253) and serum (248,251) of rodents (72, 240,252), rabbit (252), pig (252), dog (252), sheep (254), chicken (255), monkey (238,239), and man (251,253). This multiplicity has been disclosed by gel filtration (238,246,247,256), affinity chromatography (72, 86), and isoelectric focusing (242,251,257,258) as well as by kinetic studies performed on pituitary extracts and circulating gonadotropins (243)(244)(245)(246).…”
Section: Recent Studies On Fsh Pleomorphismmentioning
confidence: 99%
“…Because of the lack of a sensitive FSH bioassay, earlier investigators used radioligand receptor assays to assess FSH bioactivity (15). The receptor assay, however, cannot differentiate between agonistic and antagonistic isoforms of FSH.…”
mentioning
confidence: 99%
“…Studies with gonadotropins from different species have showvn variations in isohormone activities (11,15,16). Disparate bioto immunoactivities of different acidic FSH isoforms are believed to be due to variations in sialic acid residues that would confer a longer biological half-life and higher in vivo biopotency (3,4,17).…”
mentioning
confidence: 99%
“…Human follitropin preparations (hFSH) purified from pituitary glands or from uri nary extracts have all proved to be heteroge neous in nature [Saxena and Ratnam, 1978: Zaidi et al, 1981, 1982, This heterogeneity may be one of the reasons for the discrepancy between biological activity and immunologi cal reactivity that has been observed for many FSH preparations [ Van Damme el al., 1980;Zaidi el al., 1981Zaidi el al., , 1982, However, it was not settled whether this microhetero geneity was caused by the purification proce dures or was a characteristic of the FSH mol ecules also when present in body fluids. Wide [1981] very recently reported that FSH in sera from women of fertile ages was less acidic than FSH from men or postmeno pausal women, indicating an influence of the sex hormones on the structure of the FSH molecules.…”
mentioning
confidence: 99%